Classics in megaproject management: A structured analysis of three major works. Issue 2 (February 2018) - Pollack, Julien; Biesenthal, Christopher; Sankaran, Shankar; Clegg, Stewart
Abstract: The paper explores three texts in the field of megaproject management that intersubjectively, in terms of community sentiment, might be considered 'classics'. We deploy four criteria for a structured analysis that determines if the status of the works in question may be considered classic. The works examined are Megaprojects and Risk: An Anatomy of Ambition by Flyvbjerg, Bruzelius and Rothengatter; (2003) The Anatomy of Major Projects by Morris and Hough (1987) and Industrial Megaprojects by Merrow (2011). Based on these works we conclude with a prospectus for future research that will serve to develop the field of research into megaproject management.